Experimental HER2-Targeted Therapy Using ADAPT6-ABD-mcDM1 in Mice Bearing SKOV3 Ovarian Cancer Xenografts: Efficacy and Selection of Companion Imaging Counterpart - Javad Garousi; Tianqi Xu; Yongsheng Liu; Olga Vorontsova; Sophia Hober; Anna Orlova; Vladimir Tolmachev; Torbjörn Gräslund; Anzhelika Vorobyeva (MDPI AG, 2022)
Overexpression of the human epidermal growth factor receptor 2 (HER2) in breast and gastric cancer is exploited for targeted therapy using monoclonal antibodies and antibody-drug conjugates. Small engineered scaffold proteins, such as the albumin binding domain (ABD) derived affinity proteins (ADAPTs), are a promising new format of targeting probes for development of drug conjugates with well-defined structure and tunable pharmacokinetics. Radiolabeled ADAPT6 has shown excellent tumor-targeting properties in clinical trials. Recently, we developed a drug conjugate based on the HER2-targeting ADAPT6 fused to an albumin binding domain (ABD) for increased bioavailability and conjugated to DM1 for cytotoxic action, designated as ADAPT6-ABD-mcDM1. In this study, we investigated the therapeutic efficacy of this conjugate in mice bearing HER2-expressing SKOV3 ovarian cancer xenografts. A secondary aim was to evaluate several formats of imaging probes for visualization of HER2 expression in tumors. Administration of ADAPT6-ABD-mcDM1 provided a significant delay of tumor growth and increased the median survival of the mice, in comparison with both a non-targeting homologous construct (ADAPTNeg-ABD-mcDM1) and the vehicle-treated groups, without inducing toxicity to liver or kidneys. Moreover, the evaluation of imaging probes showed that small scaffold proteins, such as 99mTc(CO)3-ADAPT6 or the affibody molecule 99mTc-ZHER2:41071, are well suited as diagnostic companions for potential stratification of patients for ADAPT6-ABD-mcDM1-based therapy.